2018
DOI: 10.1111/jdv.15124
|View full text |Cite
|
Sign up to set email alerts
|

In situ nail unit melanoma: epidemiological and clinic‐pathologic features with conservative treatment and long‐term follow‐up

Abstract: The recognition of a NUM at an in situ stage allows early treatment and curing of this tumour. At this early stage, a 'functional surgery' is a rational approach with an excellent oncologic safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 22 publications
2
27
0
2
Order By: Relevance
“…The number of patients per study varied between 2 and 157. Nine studies were restricted to NAM in situ or minimally invasive (<0.5 mm) melanoma …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of patients per study varied between 2 and 157. Nine studies were restricted to NAM in situ or minimally invasive (<0.5 mm) melanoma …”
Section: Resultsmentioning
confidence: 99%
“…Details about gender distribution were available in 28 studies and showed a male/female ratio between 0.3–2.5 : 1 . Information on population age was given in 28 studies with a reported average age between 41.1 and 67 years (age range: 5–94 years) . A total of 818 of the NAM were located on the hand and 522 lesions on the foot.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations